A Novel Heterozygous De Novo MORC2 Missense Variant Causes an Early Onset and Severe Neurodevelopmental Disorder - Daniel Arbide; Nour Elkhateeb; Ewa Goljan; Carolina Perez Gonzalez; Anna Maw; Soo-Mi Park (Case Reports in Genetics)
Microrchidia CW-type zinc finger protein 2 (MORC2) is an ATPase-containing nuclear protein which regulates transcription through chromatin remodelling and epigenetic silencing. MORC2 may have a role in the development of neurones, and dominant variants in this gene have recently been linked with disorders including Charcot-Marie-Tooth type 2Z disease, spinal muscular atrophy and, more recently, a neurodevelopmental syndrome consisting of developmental delay, impaired growth, dysmorphic facies, and axonal neuropathy (DIGFAN), presenting with hypotonia, microcephaly, brain atrophy, intellectual disability, hearing loss, faltering growth, and craniofacial dysmorphism. Notably, variants in MORC2 have shown clinical features overlapping with those of Cockayne and Leigh syndromes. Here, we report a case of MORC2-related DIGFAN syndrome in a female infant caused by a novel heterozygous de novo variant. The condition was early onset and severe, further expanding the range of genotypes associated with this disorder. Clinical features included unilateral hearing loss, developmental delay and regression within the first year of life, microcephaly, severe feeding difficulties, and faltering growth, resulting in death at 13 months of age.